Local values in local political culture and democracy; A review of hermeneutics among local elites - Fatah, Rahmat Abd.; Arifin, Syamsul; Sudarwo, Vina Salviana Darvina; Lendriyono, Fauzik (Technium Social Sciences Journal, 2023)
The reforms provided space for local elites, both traditionally based (Bangsawan) and political elites (Bureaucrats-Politicians) to contest in the arena of local democracy. It is in this arena that the value of the political culture of local elites is tested whether it can strengthen democracy or on the contrary weaken democracy in the midst of the process towards its death.(Ziblatt, 2019) where democracy, which actually places the people as the main focal point, becomes "blunted" by political oligarchy and personal elite domination (Fatah & Deni, 2019).(Fatah & Deni, 2019). Using Gadamer's Phenomenological and Hermeneutic Methods, this research analyses the actions of local elites in interpreting the local values of Jou Se Ngofa Ngare in the 2020 Ternate City Regional Election Arena. This research aims to find the meaning of Jou Se Ngofa Ngare local values in strengthening the cultural values of local politics and democracy. The results of the study revealed that [1] The meaning of local values in local political culture and democratic values is interpreted by local elites through the process of history, pre-understanding (prejudice), tradition and value authority of leaders (Sultan / Kolano) and cultural symbols [2] The stronger the meaning and application of local values, the stronger the meaning and application of the relationship between leaders (Jou) and the people (Ngofa Ngare) in strengthening local political culture and democratic values.